Analysis Of Walking Velocity Of Pedestrian Walking Through Angled-Corridor Based On Spatial Trajectories – A Bidirectional Scenario - Jamaludin, Kamal Safwan (Universiti Sains Malaysia, 2021)
Corridors can be described as long passages used for ingress and egress routes in between buildings. Meanwhile, angled-corridors are now widely being implemented to design public facilities’ ingress and egress routes. Angled-corridors are the walkway between buildings or inside a building containing an angle or bend between the corridor ends. Typically, pedestrians tend to slow down their motion approaching a corner of the corridor. This dissertation is focusing on the effect of angled-corridor on walking pedestrian in the case on bidirectional flow. This study aims to track pedestrian's spatial trajectories while walking through angled-corridor (60°, 90° and 135°) in the case of bidirectional flow,and further to analyse their walking velocity. In achieving the objectives, the experiment the experiment of walking through angled-corridor was conducted at Dewan Serbaguna, Engineering Campus, Universiti Sains Malaysia, for two consecutive days. Three angled-corridors (60°, 90°, and 135°) were set up and three pedestrians distributions, 1-1, 15-15 and 30-30 were used to create bidirectional flow. During the experiment, participants were asked to walk freely in the angled-corridors. A GoPro camera was used to record the trajectories of the pedestrians, which were used for the tracking and analysis purpose. As a result, pedestrians’ spatial trajectories were observed and found that in terms of different angled-corridor, pedestrians in 135° walk faster than the other as the angled-corridor is an almost straight corridor and requires less turning movement from the pedestrians. Comparatively, 1 to 1, 15 to 15, and 30 to 30 simulate the conditions of relaxed, normal, and peak hours in the angled-corridors. These xiv three conditions are related to four factors affecting the velocity of the pedestrians: lane formation, space availability, lane interference, and collision avoidance. Further from the two main objectives, the velocity of pedestrians was analysed in relation to density and turning movement effect. This analysis was conducted for the range of 2-meter before and after the turning. This 2-meter distance from the turning is the tolerance distance for the pedestrians to act towards the incoming changes in the walking route. This further analysis identified that density is inversely proportional to the velocity of the pedestrians. Meanwhile, the angle opening of the corridor is directly proportional to the velocity of the pedestrians. Therefore, a bigger angle opening reduces the turning movement of the pedestrians and enhances the velocity of pedestrians. The findings of this study are expected to be a valuable fundamental for determining and designing future pedestrian facilities that include corridors with varying angles and shapes. In the future, this research should be advanced by considering various scenarios associated with turning movement at different angled-corridors.